Pengembangan UMKM Rengginang di Desa Sukakarya Kecamatan Megamendung Kabupaten Bogor melalui Pelatihan Sanitasi, Inovasi Kemasan, dan Digital Marketing - Kurniawan, Muhammad Fakih; Sadiah, Siti; Dewi, Intan Permata; Pradita, Reyna Fatma; Azzahra, Haura Luthfiya; Rajani, Afhtika Amelia; Wulandari, Fifi Yulia; Fahriza, Muhammad Nur; Rohman, Hana Fauziyyah; Aisyah, Suci; Zahro, Mutia Liza (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The existence of UMKM in the midst of society has a positive impact on their survival, especially at the economic level. To be able to continue to survive and compete, innovations are needed. One of the efforts made is to innovate the product. Products that were originally packaged simply is innovated into more modern packaging with attractive designs and brands. This is supported by a digital marketing system so that products can be known more widely. In addition, the quality and cleanliness of the product need to be considered to prevent and avoid contamination. The activities carried out were divided into three sessions, the first session on sanitation, the second session on product innovation which includes labeling and packaging, and the last session on digital marketing. The results of the discussion showed that the type of packaging used in the form of a standing pouch with the trademark